Some Geometric Properties for a Certain Class of Meromorphic Univalent Functions by Differential Operator - Lafta, Mohammed Hadi (Iraqi Journal of Science, 2021)
The major target of this paper is to study a confirmed class of meromorphic univalent functions . We procure several results, such as those related to coefficient estimates, distortion and growth theorem, radii of starlikeness, and convexity for this class, n additionto hadamard product, convex combination, closure theorem, integral operators, and neighborhoods.